Polyhydroxyalkanoate-based amphiphilic diblock copolymers as original biocompatible nanovectors1. Issue 30 (14th August 2015) - Barouti, Ghislaine; Jarnouen, Kathleen; Cammas-Marion, Sandrine; Loyer, Pascal; Guillaume, Sophie M.
<x xml:space="preserve">Abstract</x> Nanoparticles derived from poly(β-malic acid)-b-poly(3-hydroxybutyrate) (PMLA-b-PHB) copolymers revealed no cytotoxicity towards HepaRG and SK-MEL-28 cells.